Time-dependent facilitation of homologous actions - Raphael Hamel; Felix-Antoine Savoie; David Punt; Ned Jenkinson; Mark R. Hinder (Experimental Brain Research, 2026)

Multimodal nonlinear correlates of behavioural symptoms in frontotemporal dementia - Giovanna Zamboni; Irene Mattioli; Zobair Arya; Manuela Tondelli; Giulia Vinceti; Annalisa Chiari; Mark Jenkinson; Edward D. Huey; Jordan Grafman (Brain Imaging and Behavior, 2024)
Studies exploring the brain correlates of behavioral symptoms in the frontotemporal dementia spectrum (FTD) have mainly searched for linear correlations with single modality neuroimaging data, either structural magnetic resonance imaging (MRI) or fluoro-deoxy-D-glucose positron emission tomography (FDG-PET). We aimed at studying the two imaging modalities in combination to identify nonlinear co-occurring patterns of atrophy and hypometabolism related to behavioral symptoms. We analyzed data from 93 FTD patients who underwent T1-weighted MRI, FDG-PET imaging, and neuropsychological assessment including the Neuropsychiatric Inventory, Frontal Systems Behavior Scale, and Neurobehavioral Rating Scale. We used a data-driven approach to identify the principal components underlying behavioral variability, then related the identified components to brain variability using a newly developed method fusing maps of grey matter volume and FDG metabolism. A component representing apathy, executive dysfunction, and emotional withdrawal was associated with atrophy in bilateral anterior insula and putamen, and with hypometabolism in the right prefrontal cortex. Another component representing the disinhibition versus depression/mutism continuum was associated with atrophy in the right striatum and ventromedial prefrontal cortex for disinhibition, and hypometabolism in the left fronto-opercular region and sensorimotor cortices for depression/mutism. A component representing psychosis was associated with hypometabolism in the prefrontal cortex and hypermetabolism in auditory and visual cortices. Behavioral symptoms in FTD are associated with atrophy and altered metabolism of specific brain regions, especially located in the frontal lobes, in a hierarchical way: apathy and disinhibition are mostly associated with grey matter atrophy, whereas psychotic symptoms are mostly associated with hyper-/hypo-metabolism.

Evidence for a novel subcortical mechanism for posterior cingulate cortex atrophy in HIV peripheral neuropathy - John R. Keltner; Alan Tong; Eelke Visser; Mark Jenkinson; Colm G. Connolly; Alyssa Dasca; Aleks Sheringov; Zachary Calvo; Earl Umbao; Rohit Mande; Mary Beth Bilder; Gagandeep Sahota; et al. (Journal of NeuroVirology, 2020)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Motor awareness in anosognosia for hemiplegia: experiments at last! - Paul Mark Jenkinson; Aikaterini Fotopoulou (Experimental Brain Research, 2010)